2022
DOI: 10.1001/jamanetworkopen.2022.37091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Hepatitis Outbreak in Children, 2021 to 2022

Abstract: ImportanceAfter a cluster of pediatric cases of hepatitis of unknown etiology were identified in Scotland in March 2022, the World Health Organization published an outbreak alert, and more than 1010 probable cases were reported. Some cases progressed to acute liver failure and required liver transplant. Although many patients had positive results for adenovirus on polymerase chain reaction testing from whole blood samples and/or reported recent COVID-19 infection (with or without seropositivity), the precise p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…The most likely assumption supported by the current data is that the normal HAdV infections were rendered more severe by an additional cofactor such as secondary immunodeficiencies resulting from other pathogens or drugs or toxins 1,15,23,24 . Among the possible contributing factors to acute liver failure in children, abnormal innate immunity (resulting in a lack of limiting inflammatory responses leading to propagation of hepatocyte damage), has been hypothesised to play a major role 5,8,44,46,47 …”
Section: Aetiology and Risk Factorsmentioning
confidence: 71%
“…The most likely assumption supported by the current data is that the normal HAdV infections were rendered more severe by an additional cofactor such as secondary immunodeficiencies resulting from other pathogens or drugs or toxins 1,15,23,24 . Among the possible contributing factors to acute liver failure in children, abnormal innate immunity (resulting in a lack of limiting inflammatory responses leading to propagation of hepatocyte damage), has been hypothesised to play a major role 5,8,44,46,47 …”
Section: Aetiology and Risk Factorsmentioning
confidence: 71%
“…For children with acute hepatitis of unknown etiology but serum transaminases (ALT, AST) below 500 U/L, close attention should also be paid to their disease progression. If a mechanism associated with a postinfectious inflammatory process is identified, early administration of corticosteroids or immunomodulators may prevent progression to acute liver failure (Alexander and Deep, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Two years after the COVID-19 pandemic, acute hepatitis of unknown etiology in children (AHUCD) began to be reported worldwide [ 233 ]. Alexander et al reviewed a total of 22 case-control studies describing identified 1643 unknown hepatitis, with 120 children (7%) receiving liver transplants and 24 deaths (1%) [ 234 ]. The role of HAdV as a causative factor for at least some cases was theorized early and remains relevant.…”
Section: Future Projections Of Hadv Study In the 21st Centurymentioning
confidence: 99%